Light-transmitting conductive layer and light-transmitting conductive sheet

By controlling the grain size and thickness of the transparent conductive layer and combining with the transparent substrate layer, the crack problem of the transparent conductive layer when bending is solved, and a transparent conductive layer with low resistance and high flexibility is achieved, which is suitable for optical equipment.

JP7628568B2Active Publication Date: 2025-02-10NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023055609
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-02-10
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The existing transparent conductive layer is prone to cracks when bending, resulting in inflexibility and high resistance, making it difficult to meet the needs of low resistance and high flexibility.

Method used

By controlling the grain size and thickness of the transparent conductive layer, the average grain size of the grain is 105 nm or less, the maximum grain size of the grain is 110 nm or more, and the grain ratio is less than 70%. At the same time, combined with the use of the transparent substrate layer, a transparent conductive layer with low resistance and high flexibility is formed.

Benefits of technology

The transparent conductive layer is achieved with low resistance and high flexibility, which can avoid cracks when bending while maintaining good transparency and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628568000002
    Figure 0007628568000002
  • Figure 0007628568000003
    Figure 0007628568000003
  • Figure 0007628568000001
    Figure 0007628568000001
Patent Text Reader

Abstract

To provide an optically transparent conductive layer and an optically transparent conductive sheet that feature low resistance and superior bendability.SOLUTION: An optically transparent conductive layer 2 includes a first principal face 21, and a second principal face 22 facing the first principal face 21 in the thickness direction. The optically transparent conductive layer 2 has a thickness of more than 50 nm. The optically transparent conductive layer 2 includes crystal grains, and the crystal grains have an average grain size of 105 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a light-transmitting conductive layer and a light-transmitting conductive sheet. [Background technology]

[0002] Conventionally, a light-transmitting conductive sheet is known which comprises a transparent substrate and a transparent conductive layer in that order in the thickness direction. The light-transmitting conductive layer made of indium tin oxide (ITO) is used as a conductive film for forming a pattern of a transparent electrode in various devices such as a liquid crystal display, a touch panel, and an optical sensor.

[0003] On the other hand, from the viewpoint of improving the response speed of touch panels, there is an increasing demand for light-transmitting conductive sheets having a low-resistance light-transmitting conductive layer (ITO layer). Therefore, it has been proposed to increase the average crystal grain size of the crystal grains contained in the light-transmitting conductive layer to reduce the resistance (for example, see Patent Document 1 below). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-152827 A Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, in recent years, transparent conductive films are required to have low resistance and excellent flexibility.

[0006] However, the optically transparent conductive layer of Patent Document 1 has a drawback in that the average crystal grain size of the crystal grains contained therein is large, and therefore when the optically transparent conductive layer is bent, a large stress is applied to the bent portion, causing cracks, i.e., the layer has low flexibility.

[0007] An object of the present invention is to provide a light-transmitting conductive layer and a light-transmitting conductive sheet which have low resistance and excellent flexibility. [Means for solving the problem]

[0008] The present invention [1] provides a light-transmitting conductive layer having a first main surface and a second main surface opposite to the first main surface in a thickness direction, the light-transmitting conductive layer having a thickness of more than 50 nm and crystal grains having an average crystal grain size of 105 nm or less.

[0009] The present invention [2] includes the light-transmitting conductive layer according to the above [1], wherein the crystal grains include crystal grains having a maximum crystal grain size of 110 nm or more.

[0010] The present invention [3] includes the light-transmitting conductive layer according to the above [1] or [2], in which the content of crystal grains having a crystal grain size of 100 nm or more relative to the total number of the crystal grains is 70% or less.

[0011] The present invention [4] includes a light-transmitting conductive sheet comprising the light-transmitting conductive layer according to any one of the above [1] to [3], and a base layer on the side of the first main surface and / or the second main surface of the light-transmitting conductive layer. Effect of the Invention

[0012] The present invention provides a light-transmitting conductive layer having a first main surface and a second main surface opposed to the first main surface in a thickness direction, the light-transmitting conductive layer having a thickness of more than 50 nm and having crystal grains with an average crystal grain size of 105 nm or less, and therefore having low resistance and excellent flexibility.

[0013] The light-transmitting conductive sheet of the present invention includes the light-transmitting conductive layer of the present invention, and therefore has low resistance and excellent flexibility. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 shows a cross-sectional view of one embodiment of the light-transmitting conductive sheet of the present invention. [Diagram 2] Fig. 2 is a schematic diagram showing one embodiment of the method for producing the light-transmitting conductive layer and the light-transmitting conductive sheet of the present invention. Fig. 2A shows a first step of preparing a transparent substrate. Fig. 2B shows a first step of forming an optical adjustment layer on one surface in the thickness direction of the transparent substrate. Fig. 2C shows a first step of forming a hard coat layer on the other surface in the thickness direction of the transparent substrate. Fig. 2D shows a second step of arranging a light-transmitting conductive layer on one surface in the thickness direction of the substrate layer. Fig. 2E shows a third step of heating the light-transmitting conductive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] With reference to FIG. 1, one embodiment of the light-transmitting conductive layer and light-transmitting conductive sheet of the present invention will be described.

[0016] In Fig. 1, the up-down direction of the paper is the up-down direction (thickness direction, first direction), the upper side of the paper is the upper side (one side in the thickness direction, one side in the first direction), and the lower side of the paper is the lower side (the other side in the thickness direction, the other side in the first direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.

[0017] <Light-transmitting conductive sheet> As shown in FIG. 1, the light-transmitting conductive sheet 1 has a sheet shape (including a film shape) having a predetermined thickness, extends in a predetermined direction (front-rear and left-right directions, i.e., surface direction) perpendicular to the up-down direction (thickness direction), and has a flat upper surface (one side in the thickness direction) and a flat lower surface (the other side in the thickness direction). The light-transmitting conductive sheet 1 is, for example, a part of a touch panel or a light control panel provided in an optical device, that is, it is not an optical device. In other words, the light-transmitting conductive sheet 1 is a part for producing an optical device, etc., does not include an image display element such as an LCD module or a light source such as an LED, is a device that is distributed as a part alone, and is industrially applicable.

[0018] The light-transmitting conductive sheet 1 also includes a light-transmitting conductive layer 2 and a base material layer 3. The light-transmitting conductive layer 2 includes a first main surface 21 and a second main surface 22 facing the first main surface 21 in the thickness direction. That is, the light-transmitting conductive sheet 1 includes a light-transmitting conductive layer 2 and a base material layer 3 on the side of the first main surface 21 and / or the second main surface 22 of the light-transmitting conductive layer 2. Specifically, the light-transmitting conductive sheet 1 includes a light-transmitting conductive layer 2 and a base material layer 3 on the side of the second main surface 22 of the light-transmitting conductive layer 2 (the other side in the thickness direction).

[0019] The thickness of the light-transmitting conductive sheet 1 is, for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less, and for example, 20 μm or more, preferably 40 μm or more, more preferably 60 μm or more, and even more preferably 80 μm or more.

[0020] <Base material layer> The substrate layer 3 is a transparent substrate that ensures the mechanical strength of the light-transmitting conductive sheet 1 .

[0021] The substrate layer 3 has a sheet shape (including a film shape).

[0022] The base material layer 3 is disposed on the side of the first main surface 21 and / or the second main surface 22 of the light-transmitting conductive layer 2. Preferably, the base material layer 3 is disposed on the side of the second main surface 22 of the light-transmitting conductive layer 2 (the other side in the thickness direction). Specifically, the base material layer 3 is disposed on the entire surface of the second main surface 22 of the light-transmitting conductive layer 2 so as to be in contact with the second main surface 22 of the light-transmitting conductive layer 2.

[0023] The base layer 3 includes, for example, a transparent base material 31, and, if necessary, a functional layer 32. Preferably, the base layer 3 includes a transparent base material 31 and a functional layer 32 on one surface in the thickness direction and / or the other surface in the thickness direction of the transparent base material 31, and more preferably, the base layer 3 includes a transparent base material 31 and a functional layer 32 on one surface in the thickness direction and the other surface in the thickness direction of the transparent base material 31.

[0024] The thickness of the base layer 3 is, for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less, and for example, 20 μm or more, preferably 40 μm or more, more preferably 60 μm or more, and even more preferably 80 μm or more.

[0025] [Transparent base material] The transparent substrate 31 is flexible and supports the light-transmitting conductive layer 2 .

[0026] The transparent substrate 31 has a sheet shape (including a film shape).

[0027] The transparent base material 31 is made of, for example, a polymer film. Therefore, it has excellent flexibility. Furthermore, if the transparent base material 31 is made of a polymer film, the light-transmitting conductive sheet 1 has excellent production efficiency.

[0028] Furthermore, when the transparent substrate 31 is made of a polymer film, the light-transmitting conductive sheet 1 (crystalline light-transmitting conductive layer 2) may be reheated from the standpoint of imparting dimensional stability to the light-transmitting conductive sheet 1, and this light-transmitting conductive sheet 1 has excellent heat stability.

[0029] Examples of materials for the polymer film include polyester resin, (meth)acrylic resin, olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, polystyrene resin, and norbornene resin. The transparent substrate 4 is preferably a polymer film made of polyester resin from the viewpoints of flexibility, heat resistance, mechanical strength, and the like.

[0030] Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate, and preferably polyethylene terephthalate.

[0031] An example of the (meth)acrylic resin is polymethacrylate.

[0032] Examples of the olefin resin include polyethylene, polypropylene, and cycloolefin polymer.

[0033] The polymer films can be used alone or in combination of two or more kinds.

[0034] The transparent substrate 31 has a total light transmittance (JIS K 7375-2008) of, for example, 60% or more, preferably 80% or more, and more preferably 85% or more.

[0035] When the total light transmittance of the transparent base material 31 is equal to or higher than the above lower limit, the transparent base material 31 has excellent transparency.

[0036] The thickness of the transparent substrate 31 is, for example, 1 μm or more, preferably 10 μm or more, more preferably 50 μm or more, even more preferably 80 μm or more, and particularly preferably 100 μm or more, and for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less.

[0037] When the thickness of the transparent substrate 31 is within the above range, the light-transmitting conductive sheet 1 can be made thin and has excellent mechanical strength.

[0038] The thickness of the transparent substrate 31 can be measured, for example, by using a thickness meter.

[0039] [Functional Layer] The functional layer 32 is disposed on one surface and / or the other surface in the thickness direction of the transparent substrate 31. Preferably, the functional layer 32 is disposed on one surface and the other surface in the thickness direction of the transparent substrate 31.

[0040] The functional layer 32 has a sheet shape (including a film shape).

[0041] Examples of the functional layer 32 include an antiblocking layer, an optical adjustment layer, and a hard coat layer, and preferably include an optical adjustment layer and a hard coat layer.

[0042] When the functional layer 32 is an optical adjustment layer and a hard coat layer, the base layer 3 includes, for example, a transparent base material 31, a hard coat layer 33 on the other thickness-wise surface of the transparent base material 31, and an optical adjustment layer on one thickness-wise surface of the transparent base material 31. In other words, the base layer 3 includes the hard coat layer 33, the transparent base material 31, and the optical adjustment layer 34, in that order toward one thickness-wise side.

[0043] {Hard coat layer} The hard coat layer 33 is an abrasion protection layer for making the light transmissible conductive sheet 1 less susceptible to abrasions.

[0044] The hard coat layer 33 is disposed on the other surface in the thickness direction of the transparent substrate 31. Specifically, the hard coat layer 33 is disposed on the entire lower surface (other surface in the thickness direction) of the transparent substrate 31 so as to be in contact with the other surface in the thickness direction of the transparent substrate 31. The hard coat layer 33 is the bottommost layer of the light-transmitting conductive sheet.

[0045] 1, the hard coat layer 33 is disposed on the other surface in the thickness direction of the transparent substrate 31, but is not limited thereto. That is, the hard coat layer 33 may be disposed on one side in the thickness direction of the transparent substrate 31, or may be disposed in a plurality of layers. In addition, when the substrate layer 3 includes the hard coat layer 33 and an optical adjustment layer 34 described later on the same side of one side or the other side in the thickness direction of the transparent substrate 31, the stacking order is not particularly limited.

[0046] The hard coat layer 33 is formed, for example, from a hard coat composition.

[0047] The hard coat composition contains, for example, a resin and, if necessary, particles. That is, the hard coat layer 33 contains, for example, a resin and, if necessary, particles.

[0048] Examples of the resin include a thermoplastic resin and a curable resin.

[0049] An example of the thermoplastic resin is a polyolefin resin.

[0050] Examples of the curable resin include acrylic resin, urethane resin, amide resin, silicone resin, epoxy resin, melamine resin, alkyd resin, siloxane-based polymer, and organic silane condensate, and preferably, acrylic resin.

[0051] Examples of the curable resin include active energy ray curable resins that are cured by irradiation with active energy rays (eg, ultraviolet rays and electron beams) and thermosetting resins that are cured by heating.

[0052] The resins can be used alone or in combination of two or more kinds.

[0053] Examples of the particles include metal oxide fine particles and organic fine particles.

[0054] Examples of materials for the metal oxide fine particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide.

[0055] Examples of materials for the organic particulates include polymethyl methacrylate, silicone, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.

[0056] The particles can be used alone or in combination of two or more kinds.

[0057] The hard coat composition contains, for example, a resin, preferably a curable resin, more preferably an active energy ray curable resin. Specifically, the hard coat composition contains an acrylic resin.

[0058] The hard coat composition may also contain, for example, a thixotropy imparting agent, a photopolymerization initiator, a filler (e.g., organic clay), and a leveling agent in an appropriate ratio. Furthermore, the hard coat composition may be diluted with a known solvent.

[0059] To form the hard coat layer 33, a diluted solution of the hard coat composition is applied to the other surface in the thickness direction of the transparent substrate 31, and dried as necessary, as described in detail below. After drying, the hard coat composition is cured, for example, by irradiation with active energy rays.

[0060] In this way, the hard coat layer 33 is formed.

[0061] The thickness of the hard coat layer 33 is, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less.

[0062] The thickness of the hard coat layer 33 can be determined, for example, by observing a cross section of the hard coat layer 33 with a scanning electron microscope (SEM).

[0063] {Optical adjustment layer} The optical adjustment layer 34 is a layer that adjusts the optical properties (e.g., refractive index) of the light-transmitting conductive sheet 1 in order to suppress the visibility of the pattern of the light-transmitting conductive layer 2 and further suppress reflection at interfaces within the light-transmitting conductive sheet 1 while ensuring excellent transparency in the light-transmitting conductive sheet 1.

[0064] The optical adjustment layer 34 is disposed on one surface in the thickness direction of the transparent substrate 31. Specifically, the optical adjustment layer 34 is disposed on the entire upper surface (one surface in the thickness direction) of the transparent substrate 31 so as to be in contact with one surface in the thickness direction of the transparent substrate 31. The optical adjustment layer 34 is in contact with the second main surface 22 of the light-transmitting conductive layer 2.

[0065] 1, the optical adjustment layer 34 is disposed on one surface in the thickness direction of the transparent substrate 31, but is not limited thereto. That is, the optical adjustment layer 34 may be disposed on the other side in the thickness direction of the transparent substrate 31, and further, a plurality of layers may be disposed. In addition, when the substrate layer 3 includes the hard coat layer 33 and the optical adjustment layer 34 in the same direction, either on one side or on the other side in the thickness direction of the transparent substrate 31, the stacking order is not particularly limited.

[0066] The optical adjustment layer 34 is formed, for example, from an optical adjustment composition.

[0067] The optical adjusting composition contains, for example, a resin, and optionally contains particles. That is, the optical adjusting layer 34 contains, for example, a resin, and optionally contains particles.

[0068] Examples of the resin include the resins listed in the above hard coat composition, and preferred examples include melamine resins, alkyd resins, and organic silane condensates.

[0069] Examples of the particles include the particles exemplified above for the hard coat composition.

[0070] The optical adjustment composition includes, for example, a resin, preferably a curable resin, and more preferably a thermosetting resin. Specifically, the optical adjustment composition includes a melamine resin, an alkyd resin, and an organic silane condensate.

[0071] In addition, the optical adjustment composition may contain, for example, a thixotropy-imparting agent, a photopolymerization initiator, a filler (for example, organic clay), and a leveling agent in an appropriate ratio. Furthermore, the optical adjustment composition may be diluted with a known solvent.

[0072] To form the optical adjustment layer 34, a diluted solution of the optical adjustment composition is applied to one surface in the thickness direction of the transparent substrate 31, and dried as necessary, as described in detail below. After drying, the optical adjustment composition is cured, for example, by heating.

[0073] In this way, the optical adjustment layer 34 is formed.

[0074] The thickness of the optical adjustment layer 34 is, for example, 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more, even more preferably 20 nm or more, particularly preferably 30 nm or more, and for example, 1000 nm or less, preferably 500 nm or less, more preferably 100 nm or less, even more preferably 50 nm or less.

[0075] The thickness of the optical adjustment layer 34 can be calculated based on the wavelength of the interference spectrum observed using, for example, an instantaneous multi-photometer system. The thickness may also be determined by observing a cross section of the optical adjustment layer 34 with a field emission transmission electron microscope (FE-TEM).

[0076] <Light-transparent conductive layer> The light-transmitting conductive layer 2 is a transparent layer having excellent electrical conductivity.

[0077] The light-transmitting conductive layer 2 has a first main surface 21 and a second main surface 22 facing the first main surface 21 in the thickness direction. In addition, a base material layer 3 is disposed on the first main surface 21 and / or the second main surface 22 side of the light-transmitting conductive layer 2. Preferably, the base material layer 3 is disposed on the second main surface 22 side (the other side in the thickness direction) of the light-transmitting conductive layer 2. Specifically, the light-transmitting conductive layer 2 has an optical adjustment layer 34, a transparent base material 31, and a hard coat layer 33 in this order on the second main surface 22 side (the other side in the thickness direction). That is, the light-transmitting conductive layer 2 is disposed on the entire upper surface (one side in the thickness direction) of the optical adjustment layer 34 so as to contact one side in the thickness direction of the optical adjustment layer 34. The light-transmitting conductive layer 2 is the uppermost layer of the light-transmitting conductive sheet.

[0078] The first main surface 21 is exposed to one side in the thickness direction. The first main surface 21 is a flat surface.

[0079] The second main surface 22 is disposed opposite to and spaced apart from the first main surface 21 on the other side in the thickness direction. The second main surface 22 is a flat surface parallel to the first main surface 21. In this embodiment, the light transmissible conductive layer 2 includes an optical adjustment layer 34, a transparent substrate 31, and a hard coat layer 33, in that order, on the second main surface 22 side (the other side in the thickness direction).

[0080] The flat surface does not necessarily mean that the first main surface 21 and the second main surface 22 are substantially parallel planes. For example, minute irregularities and waviness that are not observable are permitted.

[0081] Examples of materials for the light-transmitting conductive layer 2 include metal oxides containing at least one metal and / or metalloid selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W. If necessary, the metal oxides may be doped with metal atoms shown in the above group.

[0082] Specific examples of the light-transmitting conductive layer 2 include indium-containing oxides such as indium tin oxide (ITO), indium gallium oxide (IGO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO), and antimony-containing oxides such as antimony tin oxide (ATO), and preferably indium-containing oxides, and more preferably indium tin oxide (ITO).

[0083] When the light-transmitting conductive layer 2 contains an indium tin composite oxide, the resistance can be reduced.

[0084] When ITO is used as the material of the light-transmitting conductive layer 2, the content of tin oxide relative to the total amount of tin oxide and indium oxide is, for example, 0.5 mass% or more, preferably 3 mass% or more, more preferably 5 mass% or more, even more preferably 8 mass% or more, and for example, 20 mass% or less, preferably 15 mass% or less, more preferably 12 mass% or less.

[0085] When the content of tin oxide is equal to or higher than the lower limit, the resistance is reduced, and when the content of tin oxide is equal to or lower than the upper limit, the light-transmitting conductive layer 2 has excellent heat stability.

[0086] The tin oxide concentration in the light-transmitting conductive layer 2 can be measured by X-ray photoelectron spectroscopy, and the tin oxide content can be calculated. The tin oxide content can also be estimated from the components (known) of the target used when forming the light-transmitting conductive layer 2 by sputtering.

[0087] The light-transmitting conductive layer 2 has crystal grains, and preferably has a plurality of crystal grains. The crystal grains are sometimes called grains.

[0088] Furthermore, the light-transmitting conductive layer 2 has a plurality of crystal grains and therefore has grain boundaries, where the grain boundaries refer to the boundaries between a plurality of adjacent crystal grains.

[0089] The grain size of the crystal grains described below is the equivalent circle diameter.

[0090] The average crystal grain size of the crystal grains is 105 nm or less, preferably 100 nm or less, more preferably 95 nm or less, and for example, 20 nm or more, preferably 40 nm or more, more preferably 60 nm or more, and even more preferably 80 nm or more.

[0091] If the average crystal grain size of the crystal grains is equal to or less than the upper limit, the crystal grains are small, and therefore the flexibility is excellent. If the average crystal grain size of the crystal grains is equal to or more than the lower limit, the resistance can be reduced.

[0092] The average crystal grain size of the crystal grains can be determined by photographing the crystal grains using a field emission transmission electron microscope (FE-TEM) and subjecting the photographed image to image analysis processing. Details are as follows: the average crystal grain size is measured by the method described in the examples below.

[0093] The crystal grains include crystal grains having a maximum crystal grain size of, for example, 100 nm or more, preferably 110 nm or more, more preferably 130 nm or more, even more preferably 150 nm or more, and particularly preferably 170 nm or more.

[0094] If the crystal grains include those having a maximum crystal grain size equal to or larger than the lower limit, the resistance can be reduced.

[0095] The maximum crystal grain size of the crystal grains is, for example, 300 nm or less, preferably 250 nm or less, and more preferably 220 nm or less.

[0096] If the maximum crystal grain size is equal to or less than the above upper limit, there are no excessively coarse crystal grains, and the bending property is excellent.

[0097] The maximum grain size of the crystal grains can be determined by photographing the crystal grains using a field emission transmission electron microscope (FE-TEM) and subjecting the photographed image to image analysis processing. Details are as follows: the maximum grain size is measured by the method described in the examples below.

[0098] In the light-transmitting conductive layer 2, the content ratio of crystal grains having a crystal grain size of 100 nm or more to the total number of crystal grains is, for example, 80% or less, preferably 70% or less, more preferably 60% or less, even more preferably 50% or less, particularly preferably 40% or less, and for example, more than 0%, preferably 5% or more, more preferably 10% or more, even more preferably 20% or more, particularly preferably 30% or more.

[0099] When the ratio of the crystal grains having a grain size of 100 nm or more to the total number of crystal grains is equal to or less than the upper limit, the bending property is excellent. When the ratio of the crystal grains having a grain size of 100 nm or more to the total number of crystal grains is equal to or more than the lower limit, the resistance can be reduced.

[0100] In the light-transmitting conductive layer 2, the content of crystal grains having a crystal grain size of 150 nm or more relative to the total number of crystal grains is, for example, 50% or less, preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, and particularly preferably 5% or less.

[0101] When the content ratio of crystal grains having a crystal grain size of 150 nm or more to the total number of crystal grains is equal to or less than the above upper limit, the flexibility is excellent.

[0102] The content ratio of crystal grains having a specific grain size or more to the total number of crystal grains can be obtained by photographing the crystal grains using a field emission transmission electron microscope (FE-TEM) and subjecting the photographed image to image analysis processing. Details are measured by the method described in the examples below.

[0103] In addition, the light-transmitting conductive layer 2 is crystalline because it has crystal grains. In other words, it is preferable that the light-transmitting conductive layer 2 does not include amorphous regions in the planar direction and includes only crystalline regions. Note that a transparent conductive layer including an amorphous region can be identified, for example, by observing crystal grains in the planar direction of the transparent conductive layer with a transmission electron microscope (TEM).

[0104] When the light-transmitting conductive layer 2 is crystalline, for example, the light-transmitting conductive layer 2 is immersed in a 5% by mass aqueous hydrochloric acid solution for 15 minutes, then washed with water and dried, and the two-terminal resistance between about 15 mm on the first main surface 21 is measured, and the two-terminal resistance is 10 kΩ or less. On the other hand, if the above-mentioned two-terminal resistance exceeds 10 kΩ, the light-transmitting conductive layer 2 is amorphous.

[0105] The total light transmittance (JIS K 7375-2008) of the light transmissible conductive layer 2 is, for example, 60% or more, preferably 80% or more, and more preferably 85% or more.

[0106] When the total light transmittance of the light-transmitting conductive layer 2 is equal to or higher than the above lower limit, the light-transmitting conductive layer 2 has excellent transparency.

[0107] The thickness of the light-transmitting conductive layer 2 is more than 50 nm, preferably 55 nm or more, more preferably 60 nm or more, even more preferably 80 nm or more, particularly preferably 100 nm or more, and most preferably 120 nm or more, and for example, 1000 nm or less, preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, particularly preferably 150 nm or less, and most preferably 130 nm or less.

[0108] When the thickness of the light-transmitting conductive layer 2 is equal to or greater than the above lower limit, the resistance can be reduced. When the thickness of the light-transmitting conductive layer 2 is equal to or less than the above upper limit, the flexibility is excellent.

[0109] The thickness of the light-transmitting conductive layer 2 can be measured by observing a cross section of the light-transmitting conductive sheet 10 using, for example, a field emission transmission electron microscope (FE-TEM).

[0110] The resistivity of the light-transmitting conductive layer 2 is, for example, 5.0×10 -4 Ω cm or less, preferably 3.0×10 -4 Ω cm or less, more preferably 2.8×10 -4 Ω cm or less, more preferably 2.6×10 -4 Ω cm or less, e.g., 0.1×10 -4 Ω cm or more, preferably 0.5×10 -4 Ω cm or more, more preferably 1.0×10 -4 Ω·cm or more.

[0111] The resistivity can be measured by a four-terminal method in accordance with JIS K7194.

[0112] The surface resistance value of the light-transmitting conductive layer 2 is, for example, 200 Ω / □ or less, preferably 80 Ω / □ or less, more preferably 50 Ω / □ or less, even more preferably 40 Ω / □ or less, particularly preferably 30 Ω / □ or less, and most preferably 25 Ω / □ or less, and is usually greater than 0 Ω / □ and greater than 1 Ω / □.

[0113] The surface resistance value can be measured by a four-terminal method in accordance with JIS K7194.

[0114] The number of light-transmitting conductive layers 2 in the light-transmitting conductive sheet 10 is not particularly limited and is, for example, 1. Specifically, the number of light-transmitting conductive layers 2 for one base layer 3 is, for example, 1.

[0115] <Method for producing light-transmitting conductive sheet> A method for producing the light-transmitting conductive sheet 1 will be described with reference to FIG.

[0116] The manufacturing method of the light-transmitting conductive sheet 1 includes a first step of preparing a base layer 3, a second step of laminating (arranging) the light-transmitting conductive layer 2 on one surface in the thickness direction of the base layer 3, and a third step of heating and crystallizing the light-transmitting conductive layer 2. In this manufacturing method, each layer is arranged in order, for example, by a roll-to-roll method.

[0117] [1st step] In the first step, the base layer 3 is prepared.

[0118] To produce the base layer 3, first, a transparent base material 31 is prepared as shown in FIG. 2A.

[0119] 2B, a diluted solution of the optical adjusting composition is applied to one surface in the thickness direction of the transparent substrate 31, and after drying, the optical adjusting composition is cured by ultraviolet irradiation or heating. Thus, an optical adjusting layer 34 is formed on one surface in the thickness direction of the transparent substrate 31.

[0120] 2C, a diluted solution of the hard coat composition is applied to the other surface in the thickness direction of the transparent substrate 31, and after drying, the hard coat composition is cured by ultraviolet light irradiation or heating. This forms a hard coat layer 33 on the other surface in the thickness direction of the transparent substrate 31. This produces the substrate layer 3.

[0121] [Second process] In the second step, as shown in FIG. 2D, the light-transmitting conductive layer 2 is laminated (placed) on one surface in the thickness direction of the base layer 3 (optical adjustment layer 34).

[0122] Examples of methods for laminating the light-transmitting conductive layer 2 include vacuum deposition, sputtering, and ion plating. Preferably, sputtering is used.

[0123] In the sputtering method, one surface in the thickness direction of the adherend (base layer 3) is placed facing a target made of the material of the light-transmitting conductive layer 2 in a chamber of a vacuum device, and gas is supplied and a voltage is applied to accelerate the gas ions and irradiate the target, causing the target material to be ejected from the target surface and laminated on the adherend surface. The base layer 3 is in close contact with the film-forming roll along the circumferential direction.

[0124] Examples of the sputtering method include a two-pole sputtering method, an ECR (electron cyclotron resonance) sputtering method, a magnetron sputtering method, and an ion beam sputtering method. A magnetron sputtering method is preferable.

[0125] Examples of power sources used in the sputtering method include direct current (DC) power sources, alternating current medium frequency (AC / MF) power sources, radio frequency (RF) power sources, and radio frequency power sources superimposed with DC power sources, and preferably DC power sources.

[0126] That is, in the second step, a DC magnetron sputtering device is preferably used.

[0127] The target may be, for example, the above-mentioned metal oxide that constitutes the light-transmitting conductive layer 2. Specifically, when ITO is used as the material for the light-transmitting conductive layer 2, a target made of ITO is used.

[0128] The horizontal magnetic field strength on the target is, for example, 10 mT or more, preferably 60 mT or more, and for example, 300 mT or less.

[0129] By setting the horizontal magnetic field strength above the target within the above range, it is possible to reduce the resistance of the light transmissible conductive layer 2.

[0130] The film formation temperature during sputtering (specifically, the temperature of the base layer 3) is, for example, 100°C or less, preferably 50°C or less, more preferably 0°C or less, even more preferably -5°C or less, and for example, -20°C or more.

[0131] If the film formation temperature during sputtering is within the above range, the base layer 3 can be sufficiently cooled and crystal growth during film formation of the light-transmitting conductive layer 2 (particularly, crystal growth in the thickness direction of the light-transmitting conductive layer 2) can be suppressed, making it easier to obtain crystal grains in the light-transmitting conductive layer 2 after the third step described below.

[0132] The air pressure inside the sputtering film formation apparatus is, for example, 1.0 Pa or less, or preferably 0.5 Pa or less, and for example, 0.01 Pa or more, or preferably 0.1 Pa or more.

[0133] The gas to be introduced (sputtering gas) may be, for example, an inert gas, preferably argon gas, or a reactive gas (for example, oxygen) may be used in combination.

[0134] The ratio of the amount of reactive gas introduced to the total amount of sputtering gas and reactive gas introduced is, for example, 0.1 flow% or more, preferably 1.0 flow% or more, more preferably 2.0 flow% or more, and for example, 10.0 flow% or less, preferably 8.0 flow% or less, more preferably 5.0 flow% or less.

[0135] By adjusting the ratio of the amount of reactive gas introduced to the total amount of sputtering gas and reactive gas introduced, the grain size of the crystal grains 6 in the light-transmitting conductive layer 2 can be adjusted.

[0136] In this way, an amorphous light-transmitting conductive sheet 1 comprising an amorphous light-transmitting conductive layer 2 and a base layer 3 is obtained.

[0137] <3rd process> In the third step, the amorphous light-transmitting conductive layer 2 is heated. For example, the amorphous light-transmitting conductive layer 2 is heated by a heating device (for example, an infrared heater and a hot air oven).

[0138] The heating temperature is, for example, 80° C. or more, preferably 110° C. or more, and for example, less than 200° C., preferably 180° C. or less. The heating time is, for example, 1 minute or more, preferably 10 minutes or more, more preferably 20 minutes or more, and for example, 24 hours or less, preferably 4 hours or less, more preferably 1 hour or less.

[0139] As a result, the amorphous light-transmitting conductive layer 2 is crystallized to form a crystalline light-transmitting conductive layer 2, as shown in FIG. 2E.

[0140] As a result, the light-transmitting conductive layer 2 is obtained, and the light-transmitting conductive sheet 1 comprising the light-transmitting conductive layer 2 and the base layer 3 is obtained.

[0141] Thereafter, the light-transmitting conductive layer 2 may be patterned. The patterning is carried out, for example, by etching.

[0142] <Action and effect> The present invention provides a light-transmitting conductive layer having a first main surface and a second main surface opposed to the first main surface in a thickness direction, the light-transmitting conductive layer having a thickness of more than 50 nm and having crystal grains with an average crystal grain size of 105 nm or less, and therefore having low resistance and excellent flexibility.

[0143] Specifically, the light-transmitting conductive layer has a thickness exceeding 50 nm, and therefore has low resistance. Furthermore, the light-transmitting conductive layer has crystal grains with an average crystal grain size of 105 nm or less, and therefore has excellent flexibility.

[0144] Furthermore, the light-transmitting conductive sheet having the light-transmitting conductive layer of the present invention has low resistance and excellent flexibility. EXAMPLES

[0145] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0146] Example 1 <Production of light-transmitting conductive sheet> [1st step] A roll of polyethylene terephthalate (PET) film (100 μm thick, manufactured by Mitsubishi Chemical Corporation) was prepared as a long transparent substrate, and a thermosetting resin composition C1 was applied to one surface in the thickness direction of the PET film to form a coating film. The coating film of the resin composition C1 was heated at 185° C. for 1 minute to be cured. This formed an optical adjustment layer having a thickness of 35 nm. The resin composition C1 is a resin composition containing 100 parts by mass of melamine resin, 100 parts by mass of alkyd resin, and 50 parts by mass of an organic silane condensate. Next, an ultraviolet-curable resin composition C2 was applied to the other surface in the thickness direction of the PET film to form a coating film. The coating film of the resin composition C2 was cured by ultraviolet irradiation. This formed a hard coat layer having a thickness of 2 μm. The resin composition C2 is a resin composition containing an acrylic resin.

[0147] In this way, a substrate layer (having a hard coat layer, a transparent substrate, and an optical adjustment layer in this order toward one side in the thickness direction) was produced.

[0148] [Second process] A 125 nm-thick amorphous light-transmitting conductive layer was laminated (placed) on one surface of the substrate layer (optical adjustment layer) in the thickness direction by reactive sputtering. In the reactive sputtering, a sputtering deposition device (DC magnetron sputtering device) capable of performing a film deposition process by a roll-to-roll method was used.

[0149] Specifically, a sintered body of indium oxide and tin oxide (tin oxide concentration: 10% by mass) was used as the target. A DC power supply was used as the power supply for applying voltage to the target. The horizontal magnetic field strength above the target was 90 mT. The transport speed of the substrate layer was 2.0 m / min. The film formation temperature (temperature of the substrate layer) was -8°C.

[0150] In addition, the ultimate vacuum level in the deposition chamber of the sputter deposition device is 0.8×10 -4 After evacuating the inside of the sputtering deposition apparatus until the inside pressure reached 0.4 Pa, argon as a sputtering gas and oxygen as a reactive gas were introduced into the sputtering deposition apparatus, and the pressure inside the sputtering deposition apparatus was set to 0.4 Pa. The ratio of the amount of oxygen introduced to the total amount of argon and oxygen introduced into the sputtering deposition apparatus was about 3.4 flow%.

[0151] This resulted in a light-transmitting conductive sheet having an amorphous light-transmitting conductive layer with a thickness of 125 nm.

[0152] [3rd step] The light-transmitting conductive sheet having an amorphous light-transmitting conductive layer was heated in a hot air oven at 155° C. for 30 minutes to crystallize the light-transmitting conductive layer.

[0153] This resulted in the production of a light-transmitting conductive sheet of Example 1, which included a light-transmitting conductive layer and a base layer on the second main surface side of the light-transmitting conductive layer (the other side in the thickness direction).

[0154] Comparative Example 1 A light-transmitting conductive sheet was obtained in the same manner as in Example 1, except that in the second step, krypton was used as the sputtering gas.

[0155] Comparative Example 2 A light-transmitting conductive sheet was obtained in the same manner as in Example 1, except that in the third step, the light-transmitting conductive sheet was not heated and the amorphous light-transmitting conductive layer was not crystallized.

[0156] <Evaluation> [Thickness of light-transmitting conductive layer] The thickness of the light-transmitting conductive layer in Example 1 and each Comparative Example was measured by field emission transmission electron microscope (FE-TEM) observation (cross-sectional observation). Specifically, first, a sample for cross-sectional observation of the light-transmitting conductive layer in Example 1 and each Comparative Example was prepared by focused ion beam (FIB) microsampling. In the FIB microsampling method, a FIB device (trade name "FB2200", manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the thickness of the light-transmitting conductive layer in the sample for cross-sectional observation was measured by FE-TEM observation. In the FE-TEM observation, a FE-TEM device (trade name "JEM-2800", manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV. The results are shown in Table 1.

[0157] [Resistance value] The resistance values ​​(R0) of the light-transmitting conductive sheets of Example 1 and Comparative Example were measured by a four-terminal method. The resistance values ​​were evaluated according to the following criteria. The results are shown in Table 1.

[0158] {standard} 〇:40Ω / □ or less ×: Exceeding 40Ω / □

[0159] [Crystal grain size (planar view)] The light-transmitting conductive sheets of Example 1 and Comparative Example 1 were cut out and fixed to a sample holder of an ultramicrotome. Next, a microtome knife was placed at an extremely acute angle to the light-transmitting conductive layer surface, and the cut surface was cut so as to be approximately parallel to the light-transmitting conductive layer to obtain an observation sample. This observation sample was photographed using a FE-TEM device (trade name "JEM-2800", manufactured by JEOL) with an acceleration voltage of 200 kV to photograph the crystal grains in a planar view of the light-transmitting conductive layer (direct magnification: 100,000 times). The photographed range was about 1400 nm x 1400 nm. Next, the photographed image was subjected to image analysis processing to determine the area of ​​each crystal grain boundary region from the number of pixels present in the region (each crystal grain boundary region) defined by the crystal grain boundary, and the diameter of a circle having the same area as the area was calculated as the crystal grain size (circle equivalent diameter), and the average crystal grain size and the maximum crystal grain size were obtained. In addition, the number of crystal grains with a crystal grain size of 100 nm or more among the crystal grains observed (photographed) by FE-TEM was determined, and the content ratio of crystal grains with a crystal grain size of 100 nm or more to the total number of crystal grains observed was determined. Similarly, the content ratio of crystal grains with a crystal grain size of 150 nm or more was determined. The results are shown in Table 1. Note that the light-transmitting conductive sheet of Comparative Example 2 is amorphous and does not have crystal grains.

[0160] [Flexibility] The light-transmitting conductive sheets of Example 1 and each of the comparative examples were cut to a width of 10 mm and a length of 150 mm. The cut light-transmitting conductive sheets were placed on the mandrel so that the light-transmitting conductive layer was on the outside and the other surface in the thickness direction of the base layer (hard coat layer) was in contact with the mandrel. Then, both ends of the light-transmitting conductive sheet in the length direction were clipped, and a weight of 1000 g was attached to the center of the clip. That is, a load of 100 g / mm was applied downward with respect to the width of the light-transmitting conductive sheet to fold the light-transmitting conductive sheet. This folded state was maintained for 10 seconds. In the folded state, the bent portion was painted with a marker, and then the folded state was released, and the painted portion was observed with a microscope. The diameter of the mandrel was changed from a large diameter to a small diameter in 1 mm increments, and the smallest diameter at which no cracks were observed in the observation of the painted portion is shown in Table 1. The smaller the diameter at which no cracks were observed, the better the bending resistance. Each time the diameter of the mandrel was changed, a new light-transmitting conductive sheet was used.

[0161] [Table 1] [Explanation of symbols]

[0162] 1. Light-transmitting transparent conductive sheet 2 Light-transparent conductive layer 3 Base material layer 21 First main surface 22 Second main surface

Claims

1. A light-transmitting conductive layer having a first main surface and a second main surface opposed to the first main surface in a thickness direction, The thickness of the light-transmitting conductive layer is greater than 50 nm; the light-transmitting conductive layer has crystal grains, The average crystal grain size of the crystal grains is 105 nm or less, The content ratio of crystal grains having a crystal grain size of 100 nm or more to the total number of the crystal grains is 5% or more and 80% or less, The optically transparent conductive layer has a specific resistance of 3.0×10 −4 Ω·cm or less.

2. The light-transmitting conductive layer according to claim 1 , wherein the crystal grains include crystal grains having a maximum crystal grain size of 110 nm or more.

3. 2. The light-transmitting conductive layer according to claim 1, wherein the content of crystal grains having a crystal grain size of 100 nm or more with respect to the total number of the crystal grains is 70% or less.

4. A light-transmitting conductive layer having a first main surface and a second main surface opposed to the first main surface in a thickness direction, The thickness of the light-transmitting conductive layer is greater than 50 nm; the light-transmitting conductive layer is made of an indium tin composite oxide; the light-transmitting conductive layer has crystal grains, The crystal grains include crystal grains having a maximum crystal grain size of 110 nm or more, The average crystal grain size of the crystal grains is 105 nm or less, The optically transparent conductive layer has a specific resistance of 3.0×10 −4 Ω·cm or less.

5. 5. The light-transmitting conductive layer according to claim 4, wherein the content of crystal grains having a crystal grain size of 100 nm or more with respect to the total number of the crystal grains is 70% or less.

6. The light-transmitting conductive layer according to any one of claims 1 to 5, a base material layer on the side of the first main surface and / or the second main surface of the light-transmitting conductive layer; A light-transmitting conductive sheet comprising:

Citation Information

Patent Citations

  • Manufacturing method of organic el element

    JP2013004368A

  • Substrate with transparent electrode and manufacturing method therefor

    JP2013152827A

  • Photovoltaic power generation element and manufacturing method therefor

    JP2015072938A

  • Transparent conductive multilayer body and touch panel

    WO2005106897A1